2021
DOI: 10.1111/deve.12267
|View full text |Cite
|
Sign up to set email alerts
|

Growth Spillovers for the MENA Region: Geography, Institutions, or Trade?

Abstract: We examine the role of spatial spillovers in economic growth for the Middle East and North Africa (MENA) region. We explicitly model spatial interactions that may arise from geography, bilateral trade, or institutional similarities, and ask how much they are likely to matter for growth externalities and spillover effects. We find that the economic growth of a MENA country is positively affected by the economic growth of countries that are geographically close and that have similar institutional characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…) thus contributes to the previous evidence on institutional proximity's significant spatial spillover effect, such as byBaysoy & Altug (2021), Ahmad, (2019,Ganau (2017),Ahmad & Hall (2017) andArbia et al (2010), and in line with other spatial studies utilizing non-geographical matrices such as those papers cited in the introduction section.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…) thus contributes to the previous evidence on institutional proximity's significant spatial spillover effect, such as byBaysoy & Altug (2021), Ahmad, (2019,Ganau (2017),Ahmad & Hall (2017) andArbia et al (2010), and in line with other spatial studies utilizing non-geographical matrices such as those papers cited in the introduction section.…”
supporting
confidence: 86%
“…This is since interdependence between countries can be a result of sociopolitical phenomena such as historically shared ties or levels of interactions, or other network structure (Beck et al 2006;Ertur & Koch, 2011). Spatial econometrics studies using non-geographical spatial matrix are gaining attention recently, such as Qu et al (2021), Amidi & Majidi (2020), and Ho et al (2018Ho et al ( , 2013)using trade-related matrices; Baysoy & Altug (2021), Ahmad, (2019), Ganau (2017), Ahmad & Hall, (2017), Arbia et al (2010) institutional proximity matrices; Zhang et al (2020), Caragliu & Nijkamp (2016) On the back of this development, this paper formally employs spatial econometrics analysis to investigate the effects of FD and institutions on the growth process of the countries under study, and this constitute the paper's first contribution to the existing FD-growth literature. Secondly, apart from using the conventional geographical-based spatial dependence, this paper extends the measure to institutional proximity concept, apparently rarely explored in the FD-growth analysis.…”
Section: Introductionmentioning
confidence: 99%
“…They found substantial spatial interactions in economic growth led to an increase in convergence rate. Baysoy and Altug (2021) explored the spatial influences on the economic growth of 18 countries in the Middle East and North Africa between 1970 and 2014. They observed that the economic growth of neighboring countries with similar institutional characteristics is positively correlated.…”
Section: Spatial Dependence Of Economic Growthmentioning
confidence: 99%
“…The region's human geography is characterised by a significant split between urban and rural lifestyles and living conditions. Prosperity, both at the individual and national level and economic performance, differs starkly between those countries with significant hydrocarbon resources and those without (Baysoy & Altug, 2021). Other challenges include exponential population growth, intense urbanisation, the uneven allocation of rudimental resources such as water and high military spending amid chronic regional conflicts.…”
Section: Introductionmentioning
confidence: 99%